2005
DOI: 10.1038/sj.onc.1208625
|View full text |Cite
|
Sign up to set email alerts
|

The antiepidermal growth factor receptor monoclonal antibody cetuximab/C225 reduces hypoxia-inducible factor-1 alpha, leading to transcriptional inhibition of vascular endothelial growth factor expression

Abstract: We have previously shown that the antiepidermal growth factor receptor monoclonal antibody cetuximab (C225; Erbitux), which was recently approved for the treatment of metastatic colorectal cancer, has antiangiogenic properties, inhibiting vascular endothelial growth factor (VEGF) secretion in culture and in animal models. Here, we have furthered the study by demonstrating that cetuximab reduces cellular levels of hypoxia-inducible factor-1 alpha (HIF-1a), a transcriptional regulator of VEGF expression, in A431… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 65 publications
7
91
0
1
Order By: Relevance
“…Expression levels of HIF-1· are known to be upregulated by activation of EGFR signaling via the PI3-K/AKT and MAPK/ERK pathways (11,(17)(18)(19)40). Our results were in accord with previous studies showing that blockade of EGFR pathways by cetuximab inhibited the expression of HIF-1· in hypoxia (25,29,(41)(42)(43)(44)(45). We showed that cetuximab-mediated down-regulation of ERK1/2 and AKT phosphorylation, especially in hypoxic gastric cancer cells, led to the downstream inhibition of HIF-1·.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Expression levels of HIF-1· are known to be upregulated by activation of EGFR signaling via the PI3-K/AKT and MAPK/ERK pathways (11,(17)(18)(19)40). Our results were in accord with previous studies showing that blockade of EGFR pathways by cetuximab inhibited the expression of HIF-1· in hypoxia (25,29,(41)(42)(43)(44)(45). We showed that cetuximab-mediated down-regulation of ERK1/2 and AKT phosphorylation, especially in hypoxic gastric cancer cells, led to the downstream inhibition of HIF-1·.…”
Section: Discussionsupporting
confidence: 90%
“…Cetuximab (C225, Erbitux) is a chimeric monoclonal antibody directed to the extracellular domain of EGFR. Numerous studies have shown that cetuximab inhibited the production of vascular endothelial growth factor (VEGF) in vitro and in vivo by inhibiting HIF-1· expression levels (24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in the present study, we observed that cetuximab partially inhibited in vivo tumor growth of the cell line that carried the mutation. It has been reported that cetuximab has the potential to inhibit angiogenesis in malignant tumors (33,34) and the potential to enhance a host's tumor immunity (35). Our results described above might reflect these actions.…”
Section: Discussionmentioning
confidence: 48%
“…In the same cell line, cetuximab reduced HIF-1α expression more distinctly as compared to the other epithelial cell lines in which only minor reduction of HIF-1α could be observed. Luwor et al proposed that mutations within the PTEN gene render cancer cells more resistant to cetuximab-mediated reduction of the HIF-1α level (130), which could also be of importance in our observations. Cell lines with primarily mesenchymal phenotype (LK0827 and LK0923) showed no effect of cetuximab on HIF-1α expression and only a few significant differences in treatment response between normoxia and hypoxia were found in these cell lines.…”
Section: The Impact Of Hypoxia On Hnscc Cell Linessupporting
confidence: 58%